Women’s Language Features in a Patriarchal Context: A Lakoffian Analysis of The Yellow Wallpaper - Dini Fatma Karomah Aljamilah; Oktavia Ramadhani; Sin Syifa Auliya; Dwi Angel Safrilla Wontolu (Fakultas Komunikasi, Sastra, dan Bahasa, 2026)
This study explores women’s language features in a patriarchal context by analyzing Charlotte Perkins Gilman’s The Yellow Wallpaper through the lens of Robin Lakoff’s (1975) framework. Focusing exclusively on the female narrator, the study examines narrative passages, sentences, and expressions to identify linguistic patterns that reflect social and ideological constraints. Using a qualitative descriptive approach, nine women’s language features were identified: lexical hedges, tag questions, rising intonation, intensifiers, hypercorrect grammar, super‑polite forms, avoidance of strong swear words, precise color terms, and empty adjectives. The findings show that these features serve to convey tentativeness, politeness, emotional expression, and psychological sensitivity, highlighting the narrator’s constrained agency under patriarchal and institutional control, particularly within the context of the rest cure. From a feminist literary perspective, the language simultaneously provides subtle means for resistance and self-expression, revealing how linguistic strategies negotiate power, uncertainty, and emotion. The study underscores the value of combining Lakoff’s sociolinguistic framework with feminist literary theory to examine how language reflects and contests gendered authority in literature. Limitations include the focus on a single narrator and one literary work, suggesting the need for comparative and corpus-based studies across genres and historical contexts. Future research could explore the relationship between women’s language features, narrative perspective, and character agency to further understand how literary language constructs female subjectivity and ideological critique.